2008
DOI: 10.1086/588221
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Evolution of Acinetobacter baumannii Strains in an Outbreak Associated With War Trauma

Abstract: The Walter Reed Army Medical Center has experienced an influx of traumatically injured patients either infected or colonized with Acinetobacter baumannii. Using multilocus polymerase chain reaction (PCR) and mass spectrometry to genotype isolates, we found an atypical and evolving strain distribution, distinct from those found at nonmilitary hospitals in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…In that study the investigators concluded that Rep-PCR was able to delineate S. pneumoniae with a discriminatory power equal to that of PFGE and suggested that it could be used as a stand-alone method for this species, with the only qualification that subtype groupings were more difficult to define by Rep-PCR. MLST with ESI-MS has been successfully used to type isolates of Streptococcus pyogenes, Acinetobacter baumannii, and Campylobacter species (8,9,13,21,38).…”
Section: Discussionmentioning
confidence: 99%
“…In that study the investigators concluded that Rep-PCR was able to delineate S. pneumoniae with a discriminatory power equal to that of PFGE and suggested that it could be used as a stand-alone method for this species, with the only qualification that subtype groupings were more difficult to define by Rep-PCR. MLST with ESI-MS has been successfully used to type isolates of Streptococcus pyogenes, Acinetobacter baumannii, and Campylobacter species (8,9,13,21,38).…”
Section: Discussionmentioning
confidence: 99%
“…(8). PCR/ESI-MS has also been employed to track epidemics of A. baumannii associated with war trauma (31). In a multiclonal collection of Acinetobacter spp., PCR/ESI-MS analysis revealed that there was significant genetic diversity among clinical isolates (14).…”
Section: Discussionmentioning
confidence: 99%
“…Sites of infection include lung, bloodstream, urinary tract, and skin (20). In addition, A. baumannii has emerged as an important pathogen in injured United States military personnel stationed in Afghanistan and Iraq as they return to major military medical treatment facilities (14,(24)(25)(26)31). …”
mentioning
confidence: 99%
“…Comparative genomic analysis of a small number of clinical A. baumannii isolates previously revealed a poor correlation between genetic relatedness and patterns of antimicrobial susceptibility (1,17,35). Furthermore, a study involving wholegenome sequence analysis of six closely related clinical isolates revealed extensive divergence of the resistance genotype, with resistance genes associated with insertion sequences, plasmids, and a chromosomal resistance gene island all showing extensive variability, suggesting rapid evolution of drug resistance (2).…”
mentioning
confidence: 99%